2022
DOI: 10.3390/ijerph19063319
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Description of Resident Physicians’ Understanding of Child Maltreatment: Impacts, Recognition, and Response

Abstract: Child maltreatment (CM) is a public health problem with devastating effects on individuals, families, and communities. Resident physicians have varied formal education in CM, and report feeling inadequately trained in identifying and responding to CM. The purpose of this study is to explore residents’ understanding of the impacts of CM, and their perceptions of their role in recognizing and responding to CM to better understand their educational needs. This study analyzed qualitative data obtained from a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Paradoxically, healthcare providers in our study reported a lack of specialized training in child maltreatment accompanied by a frequent lack of confidence in identifying and reporting child maltreatment in cases that are not clear-cut cases of assault. This finding is consistent with findings from another study conducted with Canadian medical residents ( 16 ), and this dearth of training represents a significant gap within medical education and training.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Paradoxically, healthcare providers in our study reported a lack of specialized training in child maltreatment accompanied by a frequent lack of confidence in identifying and reporting child maltreatment in cases that are not clear-cut cases of assault. This finding is consistent with findings from another study conducted with Canadian medical residents ( 16 ), and this dearth of training represents a significant gap within medical education and training.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the decision to report is more nuanced in cases with more complex medical explanations of injuries/presenting concerns or those with other elements at play such as FDIA, caregiver/teen conflict, and some supervision concerns. Extant literature similarly states that healthcare professionals tend to hesitate to refer to child welfare in cases with increased complexity ( 16 , 21 ). Oftentimes, healthcare providers attempt to mobilize supports within the healthcare setting and consult many different members of the healthcare team before making a report, as they recognize and appreciate the repercussions their report may have for the family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, health care and social service organizations are frequently unsafe, alienating, and intimidating for Indigenous peoples; a lack of trust, as well as frequent stereotyping and racism, may prevent Indigenous peoples from disclosing health-related concerns, including family violence [ 19 ]. Evidence also indicates that health care and social service providers are inadequately prepared with the knowledge, skills, and behaviors to respond to disclosures of family violence in their practice encounters [ 20 , 21 ]. Unsurprisingly, Indigenous peoples have expressed a preference to use their familial- and community-based informal support networks when experiencing violence and only use formal providers when reaching a crisis point [ 22 ].…”
Section: Introductionmentioning
confidence: 99%